A study on maintenance management of school building in Perak Tengah District / Ahmad Fahmi Che Lah and Mohd Azian Zaidi - Che Lah, Ahmad Fahmi; Zaidi, Mohd Azian (2018)
Building maintenance is a collection of a lot of activities. In order to carry out the maintenance job we may require some approvals for the work to proceed, which may vary depending on size, characteristics of the project, management style, work environment and the cooperation of all parties involved. In an ideal maintenance operation, the important parties involved in the execution of the work are the owner or the client, the contractor and the user.This study about the challenges and problem related to maintenance management of school building, identifying a current practice and issues faced by school administrator for maintaining school building and also to propose the best practice model for maintenance management of school building. Aim of this research is to propose the best possible model for maintenance management on Malaysian school building. Two main objectives to achieve the aim of this study is to identify a factor that contributed to the challenges and problem related to maintenance management of school building and a current maintenance management practice and to evaluate the level of satisfaction among end user. There are three stages in the methodology which consists of literature review in stage 1, identification of issues in stage 2, and data collection survey using questionnaire in stage 3.